The rearrangement of actin cytoskeleton in mossy fiber synapses in a model of experimental febrile seizures - Yang, Nuo; Chen, Yin-Bo; Zhang, Yan-Feng (Frontiers in Neurology, 2023)
Background Experimental complex febrile seizures induce a persistent hippocampal hyperexcitability and an enhanced seizure susceptibility in adulthood. The rearrangement of filamentous actin (F-actin) enhances the excitability of hippocampus and contributes to epileptogenesis in epileptic models. However, the remodeling of F-actin after prolonged febrile seizures is to be determined. Methods Prolonged experimental febrile seizures were induced by hyperthermia on P10 and P14 rat pups. Changes of actin cytoskeleton in hippocampal subregions were examined at P60 and the neuronal cells and pre- /postsynaptic components were labeled. Results F-actin was increased significantly in the stratum lucidum of CA3 region in both HT + 10D and HT + 14D groups and further comparison between the two groups showed no significant difference. The abundance of ZNT3, the presynaptic marker of mossy fiber (MF)-CA3 synapses, increased significantly whereas the postsynaptic marker PSD95 did not change significantly. Overlapping area of F-actin and ZNT3 showed a significant increase in both HT+ groups. The results of cell counts showed no significant increase or decrease in the number of neurons in each area of hippocampus. Conclusion F-actin was significantly up-regulated in the stratum lucidum of CA3, corresponding to the increase of the presynaptic marker of MF-CA3 synapses after prolonged febrile seizures, which may enhance the excitatory output from the dentate gyrus to CA3 and contribute to the hippocampal hyperexcitability.